Africa's Human Capital Development: Is Public Finance Management an Effective Strategy? - Fagbemi, Fisayo; Adeoye, Omowumi Grace (Journal of Social Economics Research, 2019)
Given the prevailing conjecture that human capital has multiple pathways through which it influences growth and development, understanding its current level and capacity and the public finance management impact in Africa cannot be overemphasized. Hence, the study examines the long-run and short-run relationship between public spending and human capital in twenty-one (21) sub-Saharan African (SSA) countries between 1984 and 2016 using mean – group (MG) and pooled mean – group (PMG). Empirical evidence reveals that when primary school enrollment is employed as the human capital indicator, public spending has a positive and significant effect on human capital in the long-run, whereas it is insignificant in the short-run. The findings support the view that public spending oriented towards education could lead to human capital enhancement in the long-run. Also, with the inclusion of life expectancy as the human capital measure, government expenditure positively and significantly influences human capital in the long- run as well as in the short-run, suggesting that public expenditure on the advancement of literacy rate and provision of better health facilities would stimulate human capital development in SSA. The study highlights that political and institutional failures which undermine good-quality delivery of sustainable social services (including education and healthcare services) could harm the development of human capital in the region. Thus, the paper posits that ensuring effective expenditure control and results-based funding are central to the drive towards raising the quality of human capital in Africa.